Review of Forms and Functions of Pendant Koran Manuscripts - Yoltar-Yıldırım, Ayṣin (JAOS, 2023)
Forms and Functions of Pendant Koran Manuscripts. By Cornelius Berthold. Arabische Studien, vol . 17 . Wiesbaden: Harrassowitz, 2021. Pp. x + 291, illus. €68.